The development of a smoking control activity model for all aged groups by nursing student leaders - Seaharattanapatum, Bootsakon; Jrarawattanakul, Sangtien; Pungbangkadee, Rudee; Chaiyasung, Phatcharapha; Thanomsat, Kamollabhu (Thai Journal of Nursing, 2023)
This action research aimed to develop the potential nursing student leaders and to study a smoking control activity model for all ages by nursing student leaders. A sample of 40 nursing students were purposively selected. Data were collected using the questionnaires. The research instruments were verified by five experts and index of item-objective congruence ranged from 0.60-1.00. The Kuder-Richardson reliability coefficient (KR-20) of the knowledge test regarding a smoking control activity for all ages was 0.794. Data were analyzed using descriptive statistics and paired t-test. The results of this study revealed that before intervention, 52.50% of the nursing students had moderate level of knowledge (M = 15.88, SD = 3.322), but after intervention, 72.50% had high level of knowledge (M = 25.30, SD = 1.436). Also, after intervention, the mean score of nursing students’ knowledge was higher than before intervention at p < .05 (t = 17.323). Furthermore, the smoking control activity model, the “ KARPAC ” model was developed by nursing student leaders consisting of 1) knowledge of tobacco toxicity, 2) promoting positive attitude toward smoking control; 3) role play; 4) nursing student leaders’ participation; 5) social service on smoking control; and 6) continuous implementation of smoking control activities for all aged groups